2014
DOI: 10.1093/ageing/afu014
|View full text |Cite
|
Sign up to set email alerts
|

Older patients have the most to gain from orthopaedic enhanced recovery programmes

Abstract: This is the first series in the literature to assess the role of enhanced recovery pathways in the very elderly. This study not only shows that successful fast track rehabilitation can be achieved in the very elderly population undergoing elective joint replacement surgery, but that it is this cohort of vulnerable patients who have the most to gain from such multidisciplinary recovery programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 22 publications
2
57
1
2
Order By: Relevance
“…16 However, more than 75% of those aged over 80 years had a LOS of less than four days and fast-track THA with discharge to home is feasible in most patients aged 85 years and over. Starks et al 17 found that in all age groups of THA and TKA patients, median LOS was reduced when compared with that before the introduction of a fast-track pathway. The reduction in LOS was most pronounced in patients aged 85 years and over and nearly all patients were discharged directly home.…”
Section: Pre-operative Optimisationmentioning
confidence: 99%
“…16 However, more than 75% of those aged over 80 years had a LOS of less than four days and fast-track THA with discharge to home is feasible in most patients aged 85 years and over. Starks et al 17 found that in all age groups of THA and TKA patients, median LOS was reduced when compared with that before the introduction of a fast-track pathway. The reduction in LOS was most pronounced in patients aged 85 years and over and nearly all patients were discharged directly home.…”
Section: Pre-operative Optimisationmentioning
confidence: 99%
“…Adoption of enhanced recovery protocols for hip and knee arthroplasties have reduced the LOS. 9,13-16 However, early discharge from the hospital has the potential for wound complications being managed in the community and an increase in readmissions to hospital. This was recognised by the SSI reports and National Institute for Health and Care Excellence (NICE) publication on SSI arthroplasties.…”
Section: Introductionmentioning
confidence: 99%
“…There is very persuasive evidence and experience to support the use of enhanced recovery pathways for primary hip and knee replacement patients [10,16,17,18,19]). In their recent review article, Aasvang et al [20] summarise that ERAS can be routinely applied to all hip and knee replacement patients (with no age, pre-operative functional ability, or co-morbidity restrictions) to achieve a length of hospital stay from 1-3 days with discharge to home, and a reduced incidence of cardiac and venous thromboembolism complications, and reduced postoperative delirium and cognitive dysfunction.…”
Section: Eras Outcomes In Orthopaedic Surgerymentioning
confidence: 99%
“…Enhanced replacement pathways have also been found to be feasible and safe for more complex groups of patients such as the elderly [22]. A study by Starks et al [19] found that after the introduction of an enhanced recovery pathway, the most marked decrease in length of stay was for patients aged 85 years and over, with no negative effects on morbidity and mortality rates.…”
Section: Eras Outcomes In Orthopaedic Surgerymentioning
confidence: 99%